Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.jpclett.1c01289
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Dynamics of Photoluminescent Pt(II) Dimers Probed by a Coherent Vibrational Wavepacket

Abstract: Intricate potential energy surfaces (PESs) of some transition metal complexes (TMCs) pose challenges in mapping out initial excited-state pathways that could influence photochemical outcomes. Ultrafast intersystem crossing (ISC) dynamics of four structurally related platinum­(II) dimer complexes were examined by detecting their coherent vibrational wavepacket (CVWP) motions of Pt–Pt stretching mode in the metal-metal-to-ligand-charge-transfer excited states. Structurally dependent CVWP behaviors (frequency, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 40 publications
(85 reference statements)
7
54
1
Order By: Relevance
“…Upon the photoexcitation of the 1 MMLCT state, we have observed a strong beating signal corresponding to Pt-Pt stretching CVWP motions in pyrazolate-, 2thiolpyridyl-and 2-hydroxypyridyl-bridged Pt(II) dimers. 13,26,27 Furthermore, a comparative study on the Pt-Pt stretching CVWP dynamics has been conducted in a series of structurally related 2-hydroxypyridyl-bridged Pt(II) dimers. We found that the Pt-Pt stretching CVWP generated in the Franck-Condon (FC) region can be sustained during the ISC by adding phenyl substituents on the bridging ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the photoexcitation of the 1 MMLCT state, we have observed a strong beating signal corresponding to Pt-Pt stretching CVWP motions in pyrazolate-, 2thiolpyridyl-and 2-hydroxypyridyl-bridged Pt(II) dimers. 13,26,27 Furthermore, a comparative study on the Pt-Pt stretching CVWP dynamics has been conducted in a series of structurally related 2-hydroxypyridyl-bridged Pt(II) dimers. We found that the Pt-Pt stretching CVWP generated in the Franck-Condon (FC) region can be sustained during the ISC by adding phenyl substituents on the bridging ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, optical spectroscopy ,, and quantum density functional theory (DFT) calculations were used to characterize the excited-state dynamics as a function of Pt–Pt distance following MMLCT excitation in a series of these Pt­(II) dimer complexes. X-ray transient absorption (XTA) spectroscopy and wide-angle X-ray scattering (WAXS) in solution revealed a Pt–Pt contraction of 0.3–0.5 Å following MMLCT excitation for one of the pyrazolate Pt­(II) dimer complexes. , Other studies using optical transient absorption (OTA) spectroscopy and transient absorption anisotropy spectroscopy have indirectly probed the structural dynamics by identifying vibrational coherence in a Pt–Pt stretching mode present in various MMLCT-presenting Pt­(II) “butterfly-like” dimers, which manifests as an oscillatory modulation in the OTA signal. …”
Section: Introductionmentioning
confidence: 99%
“…The energetic landscape strongly impacts the dynamic processes that can be observed theoretically, which makes selecting the appropriate functional of utmost importance. Given prior studies have demonstrated that these systems undergo fast ISC, there should be low-lying triplet states with different character from the first singlet state; per El-Sayed’s rules. ,,, This leaves CAM-B3LYP and ωB97X-D as the remaining viable options, from this analysis, for properly predicting the electronic structure. Recalling the increased agreement between the equilibrium geometry found via ωB97X-D, calculations going forward will utilize this functional.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The primary use of these platinum dimer complexes has been to induce charge transfer from the metal centers to adjacent electron-accepting ligands. Experimentally, transient absorption spectroscopy is used to observe large structural rearrangements and intersystem crossing (ISC) to long-lived triplet states; future studies will explore the possibility of further transferring the charge-separated electron coherently to additional ligands to drive additional chemical processes. To that end, a series of platinum dimers were synthesized according to a butterfly motif. , Bridging ligands connecting the platinum atoms rigidly enforce a given metal–metal separation in both the ground and excited states, with direct implications for the nature and ordering of the electronic states.…”
Section: Introductionmentioning
confidence: 99%